Consumer Trust in B2C Ecommerce Strategy for Contemporary Business Transaction is Paramount for Sustaining the Emerging Commerce Market. An Assessment of the Conduct of Consumer Trust Across Cultures and Benefits of Companies that go Ecommerce - Kwadade-Cudjoe, Francis (Transactions on Engineering and Computing Sciences, 2022)
E-Commerce has been going on since Netscape.com introduced the idea in 1995 when www was invented. Businesses / consumers that have been immersed in e-commerce transaction have reaped the benefits associated with such technological break-through, as consumers sit at comfort of their homes to transact business. However, the impediment that has hindered other businesses / consumers to transform to this technological business approach has been the trust associated with carrying out business; consumer trust across global cultures has been contentious. Authors, including Hofstede, Gefen et al. and Greenberg et al. have done research on culture differences across the globe and how these differences could affect behaviours towards accepting e-commerce for transacting business. There is therefore, the need for a global digital guideline / policy to protect all consumers and businesses that trade on the internet. Such a policy would hopefully allay the fears amongst nations’ cultures having difficulty in imbibing this wholesome technological advancement for enhanced business transaction. Conducting business transaction through brick-and-mortar approach is archaic and cumbersome and should be faded out completely.